Pengaruh Media Promosi Gizi terhadap Pengetahuan dan Sikap Gizi Seimbang Siswa SDN Sukaluyu IV Karawang: The Effect of Nutrition Promotion Media on Balanced Nutrition education and behaviour for Elementary School Students Sukaluyu IV karawang - Kayla Wulandari; Ratih Kurniasari; Eka Andriani (JURNAL GIZI DAN KESEHATAN, 2024)
The school-age period is prone to health problems that affect children's future development. One of the prevention efforts through increasing knowledge in order to achieve changes in nutritional knowledge and can reduce the problem of balanced nutrition. This study aims to determine the effect of using pocket book media, balanced nutrition pyramid and balanced nutrition spinning wheel on the knowledge and attitude of balanced nutrition of SDN Sukaluyu Karawang students. This research method is a quasi-experiment with a pre and posttest design with control group design with 33 respondents of 5th grade students of SDN Sukaluyu IV. The statistical test used was the Shapiro Wilk test. Bivariate analysis used Paired Sample T-test because the data was normally distributed. The results showed there was a significant change in knowledge using nutrition media p<0.5 and attitude p<0.05 (0.04) with the use of Pocket Book media. Conclusion, nutrition promotion media such as Pocket Books, Balanced nutrition Pyramid and Nutrition Balanced Spinning Wheel can affect elementary school children's knowledge about balanced nutrition but have no effect on attitudes.   ABSTRAK Masa usia sekolah rentan terdapat masalah Kesehatan hingga mempengaruhi perkembangan anak dimasa depan. Salah satu upaya pencegahan melalui Peningkatan pengetahuan demi mencapai perubahan dari pengetahuan gizi dan dapat mengurangi permasalah gizi Seimbang. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media buku saku, piramida gizi seimbang dan nutrition balanced spinning wheel terhadap pengetahuan dan sikap gizi seimbang siswa SDN Sukaluyu Karawang. Metode penelitian ini adalah quasi eksperiment dengan rancangan pre and posttest with control group design dengan jumlah responden sebanyak 33 siswa kelas 5 SDN Sukaluyu IV. Uji statistik yang digunakan adalah uji Shapiro Wilk. Analisis bivariat menggunakan Uji Paired Sample T-test karena data terdistribusi normal. Hasil penelitian menunjukkan terdapat perubahan pengetahuan yang signifikan menggunaan media gizi p<0.5 dan sikap p<0.05 (0.04) dengan penggunaan media Buku Saku. Kesimpulan, Media promosi gizi seperti Buku Saku, Piramida gizi Seimbang dan Nutrition Balanced Spinning Wheel dapat mempengaruhi pengetahuan anak sekolah dasar mengenai gizi seimbang namun tidak berpengaruh terhadap sikap.